Tah, Jeh: The Pragmatic Functions of Cirebonese Discourse Particles as Identity Markers in WhatsApp Communication - Dina Putri Yuliani; Otong Setiawan Djuharie; Andang Saehu (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study examines the pragmatic functions of the Cirebonese discourse particles tah and jeh in WhatsApp communication. These particles function not merely as grammatical markers but as indicators of the social and cultural identity of native Cirebon speakers. Employing a mixed-methods explanatory sequential design, this study gathered responses from 15 participants representing diverse residential backgrounds and age groups (10–40 years and above). A corpus of naturally occurring WhatsApp conversations was also analysed to investigate the particles’ pragmatic functions in authentic digital contexts. The findings reveal that tah and jeh fulfil three principal functions: (1) phatic particles that sustain social cohesion in digital interaction, (2) epistemic modality markers distinguishing uncertainty (tah) from affirmation (jeh), and (3) active markers of Cirebonese identity within digital communicative spaces. Mean Likert scores indicate strong consensus that these particles function as identity markers (M=4.4), are avoided in formal contexts (M=4.5), and are used more intensively in exchanges with fellow Cirebon speakers (M=3.9). The majority of respondents (12/15) identify tah as a marker of questioning or doubt, and jeh as a marker of affirmation. These findings contribute to the growing body of research on regional language maintenance in digital communication